Survival and metamorphosis of larvae of a portunid swimming crab Chrarybdis feriatus fed different diets. - Arcillas, Imma Connie P. (Iloilo City UPHSI, 2003)
Charybdis feriatus is an edible crab, which is of high demand both in the local and international markets. This study was conducted to determine the survival rate, effect on the molting of zoeal stages and metamorphosis to megalopa, and intermolt duration of the crab larvae fed with different diets. This study was conducted wherein the larvae of the crab, Charybdis feriatus were tested on 3 different treatments. Treatment 1 (T1), larvae were fed with Artemia alone; Treatment 2 (T2), larvae were fed with Brachonus alone; Treatment 3 (T3), larvae were fed with Artemia and Brachionus. Survival and molting were recorded daily. Physico-chemical paremeters such as salinity, temperature and dissolved oxygen were monitored. The experiment lasted for 21 days. Results showed that survival of larvae in the treatment with the combination of Artemia and Brachionus was significantly higher compared with the treatments of Brachionus alone and Artemia alone. Molting to the succeeding larval stage up to megalopa was also significantly high for the combination diet. Molting based on survival, however, showed no significant difference among the treatments. Intermolt duration in every zoeal stage ranged from 3-8 days in all diets. Larvae fed with Brachionus alone had the highest survival rate and molting rate during zoea 1 and zoea 2 stages. The diet of Artemia and Brachionus combined provided the highest survival rate and molting rate from zoea 3 up to megalopa stages.
Research II : Research Manuscripts
Keywords: Crabs